Examination of the SUPPS-P Impulsive Behavior Scale among Male and Female Youth: Psychometrics and Invariance - Pedro Pechorro; Rebecca Revilla; Victor H. Palma; Cristina Nunes; Cátia Martins; Melissa A. Cyders (MDPI AG, 2021)
The UPPS-P Impulsive Behavior Scale is one of the most used and easily administered self-report measures of impulsive traits. The main objective of this study was to examine the psychometric properties of the shorter SUPPS-P scale among a school sample of 470 youth (Mage = 15.89 years, SD = 1.00) from Portugal, subdivided into males (n = 257, Mage = 15.97 years, SD = 0.98) and females (n = 213, Mage = 15.79 years, SD = 1.03). Confirmatory factor analysis results revealed that the latent five-factor structure (i.e., Negative urgency, Lack of perseverance, Lack of premeditation, Sensation seeking, and Positive urgency) obtained adequate fit and strong measurement invariance demonstrated across sex. The SUPPS-P scale also demonstrated satisfactory psychometric properties in terms of internal consistency, discriminant and convergent (e.g., with measures of youth delinquency, aggression) validities, and criterion-related validity (e.g., with crime seriousness). Findings support the use of the SUPPS-P scale in youth. Given the importance of adolescence as a critical period characterized by increases in impulsive behaviors, having a short, valid, reliable, and easily administered assessment of impulsive tendencies is important and clinically impactful.